7. Clinical outcomes and epidemiological characteristics of bacteremia in the older population of Japan. (4th December 2021) - Nakamura, Keiji; Hayakawa, Kayoko; Tsuzuki, Shinya; Ide, Satoshi; Nomoto, Hidetoshi; Nakamoto, Takato; Yamada, Gen; Yamamoto, Kei; Ohmagari, Norio
Abstract: Background: Japan is one of the most aging societies worldwide. Because older people are highly susceptible to infectious diseases, the characteristics and clinical consequences of bacteremia in this population need clarification. Methods: Patients aged ≥ 65 years with positive blood cultures were included in this study conducted between April 1, 2015 and March 31, 2018, and divided into three groups: pre-old (65–74 years), old (75–89 years), and super-old (≥90 years) according to the criteria of the Japanese Society of Geriatrics. They were also classified based on medical exposure: community-acquired (CA), healthcare-associated (HCA), and hospital-onset (HO). Parameters retrieved from medical records were used to compare each group using the chi-square test or Fisher's exact test; factors related to mortality were identified using multivariate logistic regression analysis after controlling for the confounding effect of baseline characteristics and underlying diseases. The Bonferroni corrected P < 0.05 was deemed to be statistically significant. Results: Overall, 1716 cases of bacteremia were identified in 1415 patients. Of these, 505 cases (29.4%) were found to be due to contamination. Of the 1211 cases without contamination, 397 (32.8%) included pre-old, 658 (54.3%) included old, and 156 (12.9%) included super-old patients. HCA bacteremia increased with age, while HO bacteremia was most common in pre-old patients. Escherichia coli bacteremia was most common in super-old patients. While a central line-associated bloodstream infection was more common in pre-old patients, a urinary tract infection was more common in old and super-old patients. The 7-day mortality was 7.4%, 5.8%, and 14.2% in the pre-old, old, and super-old groups, respectively (P = 0.002). The 7-day mortality for CA, HCA, and HO bacteremia was 5.4%, 6.6%, and 9.5%, respectively (P > 0.05). Multivariate logistic regression showed that HO bacteremia (aOR: 1.76 [1.05–2.94], P = 0.028) and increasing age (aOR: 1.03 [1–1.06], P=0.038) are independent risk factors for 7-day mortality. Table Comparison of characteristics of bacteremia among the pre-old, old, super-old groups, n (%) Conclusion: The epidemiology of bacteremia differs among different older age groups; thus, these populations should not be treated as a single entity. A careful approach is needed for the optimal management of bacteremia in them. Disclosures: All Authors : No reported disclosures